Harriet Tubman - Pinkney, Andrea Davis (She persisted (Philomel Books), 2021)
"Born enslaved, Harriet Tubman rose up to become one of the most successful, determined and well-known conductors of the Underground Railroad. With her family's love planted firmly in her heart, Harriet looked to the North Star for guidance--and its light helped guide her way out of slavery. Her courage made it possible for her to help others reach freedom too." -- Amazon.com.